INNOVATIVE RESERVES OF LABOR PRODUCTIVITY IMPROVE IN NATIONAL ENTERPRISES OF SUGAR INDUSTRY - T. Kostenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Overcoming the innovative inertia and effective use of innovative reserves of labor productivity increase in domestic sugar factories is an important step towards the revival of strategically important sector for Ukraine’s economy and the key to its future development in the long run. The aim of the article is to search and study of innovative reserves of labor productivity increase in domestic enterprises of sugar industry. The international experience of innovation implementing in sugar industry enterprises is studied. The paper proves that management innovation is innovative reserves of labor productivity improve in the domestic sugar enterprises. The study analyzes overall trends of innovation development and dynamics of labor productivity in the sugar factories of Ukraine during the period of 2003-2013. The benefits and risks of laboratory tests of sugar beets and sugar are overviewed for the optimal technological mode of production installation on terms of outsourcing. The necessity and economic effectiveness of laboratory research outsourcing is proved to create the optimal technological mode of sugar production. It will improve labor productivity and quality of sugar, increase production and develop new profitable activities of sugar industry enterprises.